Kinematical analysis of forehand overhead clear stroke at the time of contact phase in badminton - Madhava Pandey, B.; Reddy, T. O.; Singh, V. (International Journal of Physiology, Nutrition and Physical Education, 2019)
The purpose of the study was to determine the relationship of joints angles with the performance of Forehand Overhead Clear stroke at the time of contact phase in Badminton. Methodology: -for the present study the sample consisted of Ten Male Indian Badminton players (Rank under 50).The age ranged of the subjects ranged Between 22 to 27 years. Angle of the body measured by kinovea in degree and performance evaluated through subjective judgment by qualified officials on the basis ofthree judges rating system. For analysis of data correlation (Pearson Correlation) test was used. The level of significance was set at 0.05 levels. Conclusion: -by the help of study it is conclude that there is significant difference was found in right wrist angle with the performance of Forehand Overhead Clear at the time of contact phase in Badminton.